N‐terminal pro‐brain natriuretic peptide level determined at different times identifies transient ischaemic attack patients with atrial fibrillation. (25th June 2013) - Purroy, F.; Suárez‐Luis, I.; Mauri‐Capdevila, G.; Cambray, S.; Farré, J.; Sanahuja, J.; Piñol‐Ripoll, G.; Quílez, A.; González‐Mingot, C.; Begué, R.; Gil, M. I.; Fernández, E.; et al.
<x xml:space="preserve">Abstract</x> Background and purpose The etiological classification of patients with transient ischaemic attack (TIA) is a difficult endeavor and the use of serum biomarkers could improve the diagnostic accuracy. The aim of this study was to correlate atrial fibrillation, the main cardioembolic etiology (CE), with different serum biomarkers measured in consecutive TIA patients. Methods The concentrations of interleukin‐6 (IL‐6), tumor necrosis factor‐alpha, neuron‐specific enolase, high‐sensitivity C‐reactive protein, IL‐1‐α and the N‐terminal pro‐B type natriuretic peptide (NT‐proBNP) were quantified in the serum of 140 patients with TIA and 44 non‐stroke subjects. Measurements were performed at different times throughout evolution: within 24 h of symptoms onset and at days 7 and 90. Results With the exception of IL‐6, all biomarkers were higher in TIA patients than in controls. NT‐proBNP was significantly related to the presence or new diagnosis of AF at all time points analyzed. Furthermore, the baseline NT‐proBNP level was significantly higher than values at the 7‐day and 90‐day follow‐up. For this reason, different cut‐off values were obtained at different times: 313 pg/ml at baseline [odds ratio (OR) = 18.99, P < 0.001], 181 pg/ml at 7 days (OR = 11.4, P = 0.001) and 174 pg/ml (OR = 8.46, P < 0.001) at 90 days. Conclusion High levels of NT‐proBNP determined during the first 3 months after a TIA were associated with AF. Consequently, this biomarker may be useful to reclassify undetermined TIA patients as having disease of CE.